2018
DOI: 10.1152/ajpheart.00146.2018
|View full text |Cite
|
Sign up to set email alerts
|

Exercise cardiac MRI unmasks right ventricular dysfunction in acute hypoxia and chronic pulmonary arterial hypertension

Abstract: Coupling of right ventricular (RV) contractility to afterload is maintained at rest in the early stages of pulmonary arterial hypertension (PAH), but exercise may unmask depleted contractile reserves. We assessed whether elevated afterload reduces RV contractile reserve despite compensated resting function using noninvasive exercise imaging. Fourteen patients with PAH (mean age: 39.1 yr, 10 women and 4 men) and 34 healthy control subjects (mean ageL 35.6 yr, 17 women and 17 men) completed real-time cardiac mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 41 publications
(56 reference statements)
2
42
0
Order By: Relevance
“…There was no significant increase in RVEDA, confirming previous observations in healthy subjects exposed to acute or subacute hypobaric hypoxia (Allemann et al, 2012;Boussuges et al, 2000) or 1 h of normobaric hypoxic breathing (Huez et al, 2005;Kjaergaard et al, 2007;Pavelescu and Naeije, 2012). This was confirmed by a more recent magnetic resonance imaging study showing unchanged RV volumes after 35 min of hypoxic breathing in healthy volunteers (Jaijee et al, 2018). However there has been a report of increased RVEDA during hypoxic breathing in healthy volunteers (Netzer et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…There was no significant increase in RVEDA, confirming previous observations in healthy subjects exposed to acute or subacute hypobaric hypoxia (Allemann et al, 2012;Boussuges et al, 2000) or 1 h of normobaric hypoxic breathing (Huez et al, 2005;Kjaergaard et al, 2007;Pavelescu and Naeije, 2012). This was confirmed by a more recent magnetic resonance imaging study showing unchanged RV volumes after 35 min of hypoxic breathing in healthy volunteers (Jaijee et al, 2018). However there has been a report of increased RVEDA during hypoxic breathing in healthy volunteers (Netzer et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, the increase in PAP or PVR caused by hypoxic breathing was mild and below cutoff values for diagnosis of PH. This was confirmed by a more recent magnetic resonance imaging study showing unchanged RV volumes after 35 min of hypoxic breathing in healthy volunteers (Jaijee et al, 2018). A re-analysis of the results after exclusion of the three subjects with a QRS >100 ms did not affect the conclusions of the study.…”
Section: Discussionsupporting
confidence: 65%
“…The technique allowed aortic and pulmonary flow acquisition at numerous exercise levels and to 'true' submaximal intensity (> 85% age predicted maximum heart rate ), having being used to assess healthy subjects and patients with surgically repaired ventricular septal defects (VSD) [55,61]. Recently, ungated real time biventricular volume and aortic and pulmonary flows were performed during exercise to moderate exercise intensity in healthy subjects and patients with pulmonary arterial hypertension, the flow volumes acquired were similar to stroke volumes acquired from biventricular volumes [100].…”
Section: Flow Acquisitionmentioning
confidence: 98%
“…Using RVEF as a surrogate of RV contractile reserve, Jaijee et al showed a decrease in RVEF with submaximal exercise in chronic PAH patients despite normal RV function at rest. 40 A separate study confirmed these findings and also showed that RV-PA coupling, as measured by stroke volume/end-systolic volume, was equally impaired with exercise in a small sample of patients with severe PAH. 41 In both studies, the key driver of poor RV contractility in patients with PAH was the inability to augment RV end-systolic volume during exercise.…”
Section: Pa 4d Flow Imagingmentioning
confidence: 61%